Green Marketing and Eco-Labeling Strategies As An Effort to Build Brand Image And Tourist Loyalty In Eco-Tourism In Indonesia - Septa Intiar; Kabul Trifiyanto; Feby Evelyna; Camelia Safitri; Tono Mahmudin (Universitas Pahlawan Tuanku Tambusai, 2026)
Eco-tourism in Indonesia faces critical challenges regarding environmental degradation, greenwashing, and shifting consumer preferences toward sustainable practices. This study examines the strategic role of green marketing mix and eco-labeling strategies in bolstering brand image and fostering tourist loyalty across key eco-tourism destinations in Indonesia. Grounded in the Stimulus-Organism-Response (SOR) framework and the Theory of Planned Structural Behavior (TPB), this empirical investigation utilizes a quantitative equation modeling (SEM-PLS) approach. Data were collected from 385 domestic and international eco-tourists visiting certified eco-tourism sites in Indonesia. The empirical findings reveal that green marketing strategies and eco-labeling significantly enhance the destination's brand image, which subsequently acts as a strong mediating mechanism in driving long-term tourist loyalty and repeat visitation. Furthermore, eco-labeling serves as a crucial signal of trust that mitigates perceived environmental risks and greenwashing skepticism among eco-conscious travelers. The theoretical contribution of this research extends the application of green branding literature to emerging market eco-tourism contexts, while the managerial implications provide actionable frameworks for eco-tourism operators, local communities, and policymakers in designing authentic, certified green experiences that balance ecological preservation with financial viability